Supramolecular Chemistry 2012
DOI: 10.1002/9780470661345.smc113
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystals: Synthesis, Structure, and Applications

Abstract: The crystal structure of a compound, the 3D orientation and organization of molecules in a highly regular manner, ultimately determines most of the fundamental physical properties of that particular material, for example, thermal stability, hygroscopicity, conductivity, and mechanical strength. Consequently, an ability to control and change the crystalline environment of a material without altering the molecular properties would be of enormous significance to both manufacturers and consumers of solid specialty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 146 publications
0
6
0
Order By: Relevance
“…The original report has been very highly cited and the structure used to illustrate the concept of crystal engineering. [20][21][22] The complementarity of the melamine and cyanuric acid units has been used to rationalise the stability and relatively poor aqueous solubility of the co-crystal. This model has been used as the basis of elegant studies of CA.M crystal growth 23 and studies of CA.M under pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The original report has been very highly cited and the structure used to illustrate the concept of crystal engineering. [20][21][22] The complementarity of the melamine and cyanuric acid units has been used to rationalise the stability and relatively poor aqueous solubility of the co-crystal. This model has been used as the basis of elegant studies of CA.M crystal growth 23 and studies of CA.M under pressure.…”
Section: Introductionmentioning
confidence: 99%
“…This section highlights the use of mechanochemistry for the assembly of complex structures, including supramolecular complexes, covalent organic frameworks (COFs), rings, and cages. An early report of mechanochemical functionalization of complex molecules was provided by Aakeröy et al, who modified cavitands by mechanochemical transformation of peripheral aldehyde groups into oximes. Reaction was complete within 5 min, in excellent yields and without any by‐products, avoiding tedious purification procedures required for solution‐made products.…”
Section: Complex Structures Framework Cages and Ringsmentioning
confidence: 99%
“…The properties of a cocrystal is typically varied from its pure components, in terms of morphology, thermal behavior, sensitivity, detonation performance and so forth. [4][5][6] According to the literature, some energetic cocrystals have been reported. For instance, Bolton et.al reported the CL-20:HMX cocrystal in a 2:1 molar ratio and the results indicated that the sensitivity of CL-20 was 30 n O /n H .…”
Section: Introductionmentioning
confidence: 99%